Four-Year Temporal Study of an Intertidal Artificial Structure in the English Channel - Jean-Claude Dauvin; Maël Deloor; Jean-Philippe Pezy; Aurore Raoux; Pascal Claquin; Aurélie Foveau (Journal of Marine Science and Engineering, 2021)
An experimental artificial structure was deployed in March 2014 on the intertidal zone of the Bay of Seine (eastern part of the English Channel), at intervals of one year until April 2018, i.e., from February 2015 onwards, two blocks were collected in April each year. This study provides an inventory of sessile and motile invertebrates living on the artificial hard-bottom and describes the stages of colonization and succession during the four-year study. A total of 84 taxa were identified including 13 sessile and 71 motile taxa. For the sessile fauna, only two taxa Balanus crenatus and Mytilus edulis had colonised the blocks in 2014, and the Taxonomic Richness (TR) was relatively stable during the next three years (between 8 and 10 taxa). The TR of the motile fauna showed an increase between 2014 (5 taxa) and 2015 (34 taxa), and then decreased from 54 taxa in 2017 to 29 taxa in 2018. The abundance of the sessile fauna was very high in 2014 due to the rapid settlement of the barnacle Balanus crenatus, which remained the dominant species throughout the study. Another barnacle Perforatus perforatus, the blue mussel Mytilus edulis and three ascidians including two non-indigenous species Perophora japonica and Corella eumyota, and Molgula sp. were also among the dominant taxa of the sessile fauna. In April 2014, the dominant motile taxa was the decapod Carcinus maenas juvenile, then in 2015 the fauna became dominated by pioneer taxa such as the amphipod of the genus Monocorophium and the tanaid Zeuxo holdichi. A reduction of mean abundance was observed in the last three years of the study, combined with diversification of the dominant species especially those of small size such as Peracarida. The study shows that the colonization of such blocks deployed on oyster tables in the intertidal zone is efficient to test the ability of building material to be colonized in this transition zone.